Politeness Strategies Used in Conversation of Balinese in Tourism Sector to Foreign Tourists at Canggu, Bali - Yoga Pratama (Universitas Sebelas Maret, 2024)
A B S T R A C T This study aims to examine the implementation of politeness strategies by four Balinese individuals working in the tourism sector while communicating with Australian and English tourists in Canggu, Bali. The research employs a descriptive qualitative approach, with data collected through non-participant observation. Brown and Levinson's theory of politeness is utilized to analyze and categorize the data. The findings reveal that the communication between the Balinese and the tourists involves four politeness strategies: bald-on record, positive politeness, negative politeness, and off-record. Among these, positive politeness and off-record strategies are the most frequently employed by the Balinese speakers. These strategies are primarily influenced by the tourists' roles as guests and customers, prompting the Balinese speakers to use direct yet polite and friendly language to satisfy the tourists. Results shows that that the objective of the Balinese as a speaker employing the politeness approach is to please the listener's face and reach a better and more relevant discourse.